Sprejemanje Prešernovih pesmi - Božič, Zoran (Slavistična revija, 2007)
Challenges in the reception of Prešeren's poems were already pointed out during the poet's lifetime. Extensive explanations of his poems and reminders about erroneous understanding demonstrate that even intellectuals have difficulties with Prešeren's poetry. Boža Krakar Vogel's study confirmed the very poor cognitive response even by the students of Slovene, despite the fact that these students highly value Prešern's poetry, which can be explained by the mythical dimensions of the national poet. The comparison between Krst pri Savici (The Baptism on the Savica) and Jenko's Ognjeplamtič shows why Prešeren's romantic poem is more challenging fot reception, which was confirmed by the empirical study conducted in the first year of a secondary school, the outcame of which showed an exceptionally poor understanding of the Baptism.
Keywords: Jenko, Simon, 1835-1869; Jenko, Simon: Ognjeplamtič; Prešeren, France, 1800-1849; Prešeren, France: Krst pri Savici; razumevanje; recepcija; Slovene literature; slovenska književnost; slovenska poezija